KAJIAN KESUKSESAN E-COMMERCE (STUDI KASUS : DARULHAQ.COM) - Suharyanto Suharyanto (LPPM Nusa Mandiri, 2017)
E-commerce business in Indonesia is currently Singer Already Very lively Once Where service provider Operates online transactions vying for interesting review customer service different ads and Best Shape Of The online transaction system is provided. A different study was conducted to review Seeing the extent of the success of e-commerce successful done by the program provides services Transaction to Operate the online. The number of online transactions service provider The Challenges Becomes the Business Performer e-commerce system to review Continue to improve their e-commerce applications so that customer loyalty ON their differences. Research The author did singer is to review Seeing the extent of the success of e-commerce succeeded do Model Where Research The at developed research singer describes the variables that affect the successful implementation of e-commerce Satisfaction Of use web e-commerce Against Page http: / /www.darulhaq .com. General Operating Model Research Made Singer refers to the method Molla and Licker 2001. Variables Used hearts Research Research is an adaptation Singer Of Model Molla and Licker operates overall. Searching Google Pages Data Processing performs multiple linear regression variables Against Quality Systems, Quality Content, Trust, Support Services, the Customer Satisfaction to review Test the following hypotheses: H0: There are thought to significantly influence the Quality System, Content Quality, Trust, Service Support Operations Together Against Customer Satisfaction. Ha: There are thought to significantly influence the Quality System, Content Quality, Trust, Service Support Operations Together Against Customer Satisfaction.